How does cross-functional cooperation influence organizational performance? The mediating role of management accounting systems - Tu Thanh Hoai; Nguyen Phong Nguyen (Cogent Business & Management, 2021)
Interfirm cooperation and its linkage to management accounting information are vital for organizational performance. However, the literature lacks insight into how competitive advantage emerges in the context of intrafirm cooperation via the use of management accounting systems (MAS). This study evaluates whether management accounting practices translate cooperation among different organizational functions into enhanced organizational performance. Findings from survey data from 186 large firms in Vietnam show that the use of MAS fully mediates the effects of cross-functional cooperation on organizational performance. Our study adds to the limited research examining the interface between cross-functional cooperation and MAS.
Keywords: 650; Management accounting systems use; cross-functional cooperation; organizational performance; emerging market; Vietnam